Utilization of Ash and Potassium Extracted from Empty Palm Oil Bunch Ash for Source of Potassium to Plant: - Ritthong, Ratimawadee; Poonpakdee, Chakkrit; Khawmee, Khwunta; Onthong , Jumpen (YRU Journal of Science and Technology, 2025)
Currently, empty palm oil bunches, which high potassium (K) content, are widely used as biomass for production processes in industrial factories and power plants in the southern region. This has resulted in an increasing amount of ash, a by-product of combustion, which needs to be disposed or utilized. Nowadays, K in ash was extracted and used for sources of K to plant. The objective was to study the effects of ash and K extracted from ash of empty palm oil bunch (PEA) as a K source on plant growth and nutrients uptake. The experimental design was a completely randomized design with 4 treatments and 4 replications: 1) control (no applied K fertilizer), 2) KCl, 3) ash (empty palm oil bunch), and 4) PEA applications. Various K sources were applied by top dressing at a rate of 100 mg K2O/kg. Sweet corn of the Super Sweet variety was grown as a test crop in the Thung Wa soil series, which is characterized by coarse textural soil with low nutrients content, especially low K level. The results showed that K application not only increased the height, stem diameter, fresh weigh, and dry weight of the sweet corn, but also promoted nutrients uptake, particularly K. The growth of sweet corn applied ash, PEA, and KCl was not different. However, the application of ash and PEA not only promoted Ca and Mg in plants but also increased soil pH, K, and Ca. Therefore, ash and PEA can be used for alternative K source to plant.